Organizational Commitment As Intervening Variable of Intrinsic and Extrinsic Motivation to Organizational Citizenship Behavior - ., Mukhodah; Ranihusna, D (KnE Social Sciences, 2018)
This study aims to determine the influence of intrinsic motivatio and extrinsic motivation on organizational citizenship behavior with organizational commitment as intervening variable of the employees in PT. Sidomuncul Pupuk Nusantara Semarang. This research is quantitative research. The population in this research is 85 employees. Sampling in this research using saturated sampling system obtained sample size that must be used is 85 employees. Analytical methods used are instrument test (validity and reliability), classical assumption test, multiple linear regression test, and path analysis test. Data collection method using observation, interview, questionnaire, and library study. The results of this study indicate that Intrinsic and Extrinsic Motivation has positive and significant effect on Organizational Citizenship Behavior. Intrinsic and Extrinsic Motivation has positive and significant effect on Organizational Commitment. Organizational Commitment has positive and significant effect on Organizational Citizenship Behavior. Organizational Commitment can mediate the relationship between Intrinsic and Extrinsic Motivation on Organizational Citizenship Behavior through. The findings of this study implicate the researchers and the manager to increase and optimize intrinsic motivation, extrinsic motivation, and organizational commitment so that employees have a high OCB Keywords: Extrinsic Motivation; Intrinsic Motivation; Organizational Citizenship Behavior ;Organizational Commitment